Development of research on nursing diagnoses in Brazilian graduate programs - Gisele Saraiva Bispo Hirano; Camila Takáo Lopes; Alba Lucia Bottura Leite de Barros
ABSTRACT Objective: to characterize the development of research on nursing diagnoses in nursing graduate programs and verify the application of the results of these studies according to the perception of academic advisors. Methods: documental research on dissertations and theses available from the databases of Brazilian universities with graduate programs in nursing, and exploratory survey on the practical application of their results. Results: 216 dissertations and theses were analyzed. Most of them were descriptive studies, and the most widely used diagnostic taxonomy was NANDA International. Little practical use of the knowledge produced by the dissertations and theses was identified. Conclusion: Although there has been a considerable increase in research on nursing diagnoses, the survey stage revealed scarce practical application of their results, prompting the need for further studies in order to identify the barriers in the way of transposing theory to practice.